Impact of Fecal Calprotectin Measurement on Decision-making in Children with Inflammatory Bowel Disease - El-Matary, Wael; Abej, Esmail; Deora, Vini; Singh, Harminder; Bernstein, Charles N. (Frontiers in Pediatrics, 2017)
Background: The use of fecal calprotectin (FCal) as a marker of intestinal inflammation, in the management of inflammatory bowel disease (IBD) is increasing. The aim of this study was to examine the impact of fecal calprotectin measurements on decision making and clinical care of children with IBD. Methods: In a cohort study, FCal, clinical activity indices, and blood markers were measured in children with established diagnoses of IBD. Pearson correlation coefficient analysis was performed to examine association between FCal and other markers. Decisions based on FCal measurements were prospectively documented and participants were evaluated 3-6 months later. Results: A total of 115 fecal samples were collected from 77 children with IBD (median age 14, interquartile range (IQR) 11-15.6 years, 42 females, 37 with Crohn’s disease). FCal positively correlated with clinical activity indices (r=0.481, P<0.05), and erythrocyte sedimentation rate (r=0.40, P<0.05) and negatively correlated with hemoglobin (r= -0.40, P<0.05). Sixty four out of 74 (86%) positive FCal measurements ( ≥250 mcg/g of stools) resulted in treatment escalation with subsequent significant clinical improvement while in the FCal negative group, 34 out of 41 (83%) measurements resulted in no change in treatment and were associated with remission on follow up. Conclusions: Based on high FCal, the majority of children had treatment escalation that resulted in clinical improvement. FCal measurements were useful and reliable in decision making and clinical care of children with IBD.